Towards Sustainable Food Security in Peri-Urban Areas of Sidoarjo District - Alfarizi, Muhammad; Prayitno, Gunawan; Hidayat, AR Taufiq (Fakultas Teknik Universitas Brawijaya, 2025)
This study aims to assess the capability and capacity of agricultural land in the peri-urban areas of Sidoarjo District from 2010 to 2029. Methodologically, six capacity indices are reinterpreted as a governance-focused resilience dashboard for urban food systems. The patterns of collocation among components reveal critical pressure and leverage points, informing intervention priorities such as land protection, demand management, service density enhancement, and regional productivity improvement. Using spatial approaches, projections, and policy analysis, it was found that most indicators showed a decline in land capacity. In addition, there was a decrease in the percentage of agricultural land from 34% in 2009 to 20% in 2029. These findings underscore the importance of sustainable spatial planning and the protection of agricultural land in maintaining long-term food security and environmental sustainability. Future research should emphasize interdisciplinary collaboration, policy integration, and resilience to climate change to better address the complexities of peri-urban development.